Influence Of Offline And Online Service Facilities ToCommunity Satisfaction In Population And CivilRegistration Office Kutai Kartanegara Regency EastKalimantan - Wahyudiyono, Wahyudiyono; Albashori, Muhammad Fatkhurohman; Patriara, Rosi (Maneggio, 2024)
This study aims to analyze the influence of offline and online service facilities on community satisfaction in Kutai Kartanegara Regency, East Kalimantan. This study is a quantitative research by taking data through a questionnaire given to 100 respondents (samples) from a population of 788,113 who are occupied by Kutai Kartanegara district, East Kalimantan. The independent variable in this study is offline and online service facilities while the bound variable is the level of community satisfaction. The data obtained was analyzed with SPSS. The results of the study stated that the Offline Service Facility variable (X1) had a partial influence on the Community Satisfaction variable (Y) because the T value of X1 (7.768) > T table (1.98472) and Online Service Facility (X2) had a partial influence on the Community Satisfaction variable (Y) because the T value of X2 (5.867) > T table (1.98472). From the results of the F Test, it was obtained that the variables of Offline Service Facilities (X1) and Online Service Facilities (X2) had a simultaneous influence on the variables of Community Satisfaction (Y) because the results of the F value calculated (202.307) > F table (3.09). Meanwhile, from the results of the termination test (R Square), it was explained that the influence of the independent variable on the bound variable was 80.7%.